Analisis Penutupan Kartu Kredit Menggunakan Metode Analytical Hierarchy Process dan Preference Ranking Organization Methode for Enrichment Evaluation - Gerry Geraldicky; Viny Christanti Mawardi; Tri Sutrisno (Fakultas Teknologi Informasi Universitas Tarumanagara, 2021)
The rapid development in Indonesia is information technology. Today's computer technology can collaborate with other fields of science. One of them is a Computer Based Decision Support System (DSS). Decision Support System (DSS) is a system that is useful for increasing effectiveness in terms of decision making. A credit card is a payment instrument in the form of a card that has a credit facility to the owner in lieu of cash payment, where at maturity it can be paid with the minimum payment amount and the rest is used as credit. In applying for credit card closure, it can be combined with a decision support system. The decision support system for this case uses the Analytical Hierarchy Process (AHP) method and the Preference Ranking Organization Methods for Enrichment Evaluations (Promethee). The Analytic Hierarchy Process (AHP) method has proven its reliability in weighting the criteria value and the Preference Ranking Organization Methods for Enrichment Evaluations (Promethee) is used to rank the alternatives provided. Establishing this decision support system will produce fast and accurate recommendations to credit card management on this issue.